2012
DOI: 10.1080/0312407x.2011.597867
|View full text |Cite
|
Sign up to set email alerts
|

User and Carer Experiences of International Social Care Workers in England: Listening to their Accounts of Choice and Control

Abstract: This paper develops a typology of people using social care services' preferences for care workers and satisfaction with social care services from a large multimethod study that explored international recruitment to the English social care sector (home and health care, including residential homes). We developed this typology with two questions in mind: (a) what led to satisfaction of care and (b) what led to preference and satisfaction with workers? Data were collected from face-to-face interviews with 35 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Few studies explored the experiences of service users in relation to social care provided by migrant workers (Manthorpe et al, 2012a ; Manthorpe et al, 2012b ; Walsh & Shutes, 2013 ). Manthorpe et al ( 2012b ) identified four ‘ideal types’ in terms of satisfaction with care and preference for British care workers. While some service users voice openly racist and discriminatory views and preferences for care workers, many people are more cautious in expressing such views.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies explored the experiences of service users in relation to social care provided by migrant workers (Manthorpe et al, 2012a ; Manthorpe et al, 2012b ; Walsh & Shutes, 2013 ). Manthorpe et al ( 2012b ) identified four ‘ideal types’ in terms of satisfaction with care and preference for British care workers. While some service users voice openly racist and discriminatory views and preferences for care workers, many people are more cautious in expressing such views.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies explored the experiences of service users in relation to social care provided by migrant workers (Manthorpe et al, 2012a;Manthorpe et al, 2012b;Walsh & Shutes, 2013). Manthorpe et al (2012b) identified four 'ideal types' in terms of Fig. 2 Themes identified in the literature satisfaction with care and preference for British care workers.…”
Section: Service User Outcomesmentioning
confidence: 99%
“…Yet, globally now, such workers make a significant contribution to services in the global economy of care (Kofman et al, 2005). Improvements need to be made in the receiving countries' understanding and appreciation of the skills that migrant professionals bring and to challenge the racism that may often underpin discrimination experienced (Manthorpe, Hussein, Stevens, & Moriarty, 2011). That the nature of social work practice is determined by its local context is beyond question.…”
Section: Implications For the Professionmentioning
confidence: 99%
“…It is no surprise that one of the main motives to move to England among migrants from the Philippines was to build on previous work and skills, as the global demand for nurses (in social care as well as healthcare) has generated a rapidly growing nursing education sector for export in the Philippines with an estimated 85 % of its nurses currently working overseas (Lorenzo et al 2007). Older people and their carers may appreciate such skills (Manthorpe et al 2011) and may be encouraged that the stated motives behind migration further relate to positive views of England and what it has to offer.…”
Section: Discussionmentioning
confidence: 99%